Reading Victorian Fiction - Blake, Andrew. author. aut Link
IX, 201 p.
Keywords: A study of the interrelationship of the Victorian novel with other forms of writings, arguing that the whole literary culture was concerned with the production of Victorian values, including novels, an active part in the compromise between aristocratic and middle class cultures in this period.